The effects of centralizing cancer surgery on postoperative mortality: A systematic review and meta-analysis. Issue 4 (October 2021) - Grilli, Roberto; Violi, Federica; Bassi, Maria Chiara; Marino, Massimiliano
Objectives: To review the evidence of the effects of centralization of cancer surgery on postoperative mortality. Methods: We searched Medline, Embase, Cinahl, Cochrane and Scopus (up to November 2019) for studies that (i) assessed the effects of centralization of cancer surgery policies on in-hospital or 30-day mortality, or (ii) described changes in both postoperative mortality for a surgical intervention and degree of centralization using reduction in the number of hospitals or increases in the proportion of patients undergoing cancer surgery at high volume hospitals as proxy. PRISMA guidelines were followed. We estimated pooled odds ratios (OR) and conducted meta-regression to assess the relationship between degree of centralization and mortality. Results: A total of 41 studies met our inclusion criteria of which 15 evaluated the effect of centralization policies on postoperative mortality after cancer surgery and 26 described concurrent changes in the degree of centralization and postoperative mortality. Policy evaluation studies mainly used before-after designs (n = 13) or interrupted time series analysis (n = 2), mainly focusing on pancreatic, oesophageal and gastric cancer. All but one showed some degree of reduction in postoperative mortality, with statistically significant effects demonstrated by six studies. The pooled odds ratio for centralization policy effect was 0.68 (95% Confidence interval: 0.54–0.85; I 2 = 80%). Meta-regression analysis of the 26 descriptive studies found that an increase of the proportion of patients treated at high volume hospitals was associated with greater reduction in postoperative mortality. Conclusions: Centralization of cancer surgery is associated with reduced postoperative mortality. However, existing evidence tends to be of low quality and estimates of the effect size are likely inflated. There is a need for prospective studies using more robust approaches, and for centralization efforts to be accompanied by well-designed evaluations of their effectiveness.